2015
DOI: 10.1007/s12035-015-9357-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-kappaB-Dependent Sestrin2 Induction Mediates the Antioxidant Effects of BDNF Against Mitochondrial Inhibition in Rat Cortical Neurons

Abstract: Brain-derived neurotrophic factor (BDNF), in addition to its neurotrophic action, also possesses antioxidant activities. However, the underlying mechanisms remain to be fully defined. Sestrin2 is a stress-responsive gene implicated in the cellular defense against oxidative stress. Currently, the potential functions of sestrin2 in nervous system, in particular its correlation with neurotrophic factors, have not been well established. In this study, we hypothesized that BDNF may enhance sestrin2 expression to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 47 publications
4
47
0
Order By: Relevance
“…Nevertheless, it has been shown that treatments with phosphodiesterase-5 inhibitors (sildenafil or vardenafil), which selectively blocks degradation of cGMP, improved neurologic scores and reduced loss of striatal lesion volumes that were produced by the systemic infusion of 3-NP in rats and, importantly, the striatal expression of BDNF was significantly increased in the sildenafil-treated rats [66]. This in vivo study appears to be consistent with our contention that the cGMP/PKG pathway is important for the neuroprotective effects against 3-NP toxicity in vitro [20,31]. Previous studies have also demonstrated that 3-NP exposure may reduce the tissue contents of BDNF in vivo.…”
Section: Experimental Evidence Supporting Bdnf-mediated Neuroprotesupporting
confidence: 78%
See 4 more Smart Citations
“…Nevertheless, it has been shown that treatments with phosphodiesterase-5 inhibitors (sildenafil or vardenafil), which selectively blocks degradation of cGMP, improved neurologic scores and reduced loss of striatal lesion volumes that were produced by the systemic infusion of 3-NP in rats and, importantly, the striatal expression of BDNF was significantly increased in the sildenafil-treated rats [66]. This in vivo study appears to be consistent with our contention that the cGMP/PKG pathway is important for the neuroprotective effects against 3-NP toxicity in vitro [20,31]. Previous studies have also demonstrated that 3-NP exposure may reduce the tissue contents of BDNF in vivo.…”
Section: Experimental Evidence Supporting Bdnf-mediated Neuroprotesupporting
confidence: 78%
“…In our recent study [20], we validated the hypothesis that BDNF may increase sestrin2 expression to convey the protective effect against oxidative stress induced by 3-NP and demonstrated the molecular mechanisms of BDNF to induce sestrin2 expression in rat primary cortical cultures. In this work, we demonstrated that the NO/PKG-1 signaling pathway is engaged in BDNF-mediated sestrin2 induction [20]. It was known that PKG is a member of AGC family of serine/threonine protein kinases.…”
Section: Sestrin2 Induction Conducts the Antioxidant Effects Of Bdsupporting
confidence: 59%
See 3 more Smart Citations